Fully integrated W-CDMA IF receiver and IF transmitter including IF synthesizer and on-chip VCO for UMTS mobiles - Thomann, Wolfgang; Fenk, Josef; Hagelauer, Richard; Weigel, Robert (IEEE Journal of Solid-State Circuits, 2001)
A fully integrated, dual intermediate frequency (IF) receiver and an IF transmitter, each with on-chip IF synthesizer, for use in third-generation wide-band code division multiple access (W-CDMA) mobiles has been implemented in a standard, high-frequency, Si-bipolar process with an fT of 25 GHz. The IF receiver (318 MHz) and IF transmitter (285 MHz) include a complete phase-locked loop (PLL) and on-chip voltage-controlled oscillator (VCO) with integrated varactors and transformers. The VCOs are used for on-chip local oscillator (LO) generation and operate at four times IF, 1272 MHz and 1140 MHz, for Rx and Tx, respectively. Fully integrated, active, analog base-band filters further increase functionality and integration level. In the receiver, a channel select filter, composed of a fifth-order Chebyshev lowpass filter and a first-order all-pass filter, is implemented. In the transmitter, a fifth-order Butterworth low-pass filter functions as a reconstruction filter. Both devices operate on 2.7-3.3-V supply. The designs comply with ARIB W-CDMA and UMTS standards. Each chip is mounted in a small outline, 32-pin, leadless surface mount package.
elib2cris::1512001600,thomann2001c
Keywords: Analog base-band filter; analog integrated circuit; decibel-linear IF VGA; dual IF receiver; IF synthesizer; IF transmitter; on-chip VCO; UMTS; W-CDMA